Comparison of antimicrobial effectiveness between methanolic crude extract of three different parts of allamanda cathartica / Nur Hazwani Badrol - Badrol, Nur Hazwani (2018)
An issue on emergence of drug resistance bacteria were become a serious problem which make the antibiotics become less effective to inhibit the growth of pathogenic microbial. The aim of this study was to screen antimicrobial properties on different parts of Allamanda cathartica between different types of pathogenic microbes which are Escherichia coli (E. coli), Klebsiella pneumonia (K. pneumoniae), Staphylococcus aureus(S. aureus), Penicillium, Fusarium and Rhizopus using its flower, stem, and leaves. This study also aim to determine the Minimum Inhibitory Concentration (MIC) value of Allamanda cathartica as antimicrobial. The result of this study demonstrated that the flower extract of Allamanda was the most effective parts to inhibit the growth of pathogenic bacteria which are E. coli and S. aureus at all concentration ranging from 100 mg/ml to 1000 mg/ml. Stem extract exhibit inhibition zones of for both bacteria at higher concentration which are 500 mg/ml and 1000 mg/ml. This study also showed that plant extract failed to displayed any antimicrobial activities towards Klebsiella pneumonia and all tested fungi which are Penicillium, Fusarium, and Rhizopus. Moreover, the Minimum Inhibitory Concentration (MIC) value of Allamanda cathartica flower extract for E. coli was 62.5 mg/ml, K. pneumoniae was 250 mg/ml and S. aureus was 125 mg/ml. Hence, it is conclude that Allamanda cathartica flower extract were most effective parts to inhibit the growth of Escherichia coli and Staphylococcus aureus at all concentration given. However, Klebsiella pneumonia and the tested fungi are not inhibited by the Allamanda cathartica crude extract at all concentration tested.